7 principles of transformational leadership : - Blane, Hugh (Career Press, 2017)
In the world of work, the single greatest asset of successful individuals, teams, and organizations is their mindset―what happens in between their ears. It’s not the corporate strategy, the sales compensation plan, or the market segments they’re pursuing. It is what each leader, team member, and employee chooses to focus on, believe, and create for themselves and others. 7 Principles of Transformational Leadership presents the fundamental concepts whose implementation will result in dramatic revenue, performance, and relationship growth.